Rotary Ultrasonic Machining of Rocks: An Experimental Investigation - Fernando, Pksc; Zhang, Meng; Pei, Zhijan (My University, 2018)
Rock drilling is widely used to explore and mine energy resources. It has also been used to extract samples to study the earth’s geological composition and topography and to explore different planets. Percussive drilling is, as of right now, the most commonly used rock drilling method. Due to the high hardness and abrasiveness of rock, tool wear in rock drilling is severe, thus limiting its penetration rate and resulting in high cost. Therefore, it is crucial to develop more costeffective rock drilling processes. Rotary ultrasonic machining has been used to drill many materials including metal alloys, ceramics, and composites, and its cost advantages have been demonstrated in many previous studies. This article presents the first experimental investigation of rotary ultrasonic machining of rocks. Three types of rocks (basalt, marble, and travertine) were used. Six input variables (tool rotation speed, feedrate, ultrasonic power, abrasive size, abrasive concentration, and drill bit diameter) were examined and two output variables (cutting force and surface roughness) were measured. Results indicate that rotary ultrasonic machining can drill holes of high quality on rocks of different hardness with a much lower cutting force and at a penetration rate of approximately three times faster than percussive drilling.
Citation: Fernando, P., Zhang, M., & Pei, Z. (2018). Rotary ultrasonic machining of rocks: An experimental investigation. Advances in Mechanical Engineering, 10(3), 168781401876317. https://doi.org/10.1177/1687814018763178
Keywords: Basalt; Marble; Rock drilling; Rotary ultrasonic machining; Travertine